2014
DOI: 10.1017/hpl.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Optimal laser intensity profiles for a uniform target illumination in direct-drive inertial confinement fusion

Abstract: A numerical method providing the optimal laser intensity profiles for a direct-drive inertial confinement fusion scheme has been developed. The method provides an alternative approach to phase-space optimization studies, which can prove computationally expensive. The method applies to a generic irradiation configuration characterized by an arbitrary number N B of laser beams provided that they irradiate the whole target surface, and thus goes beyond previous analyses limited to symmetric configurations. The ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…It has recently been shown that uniform solutions of the illumination model can be obtained for any general laser–capsule configuration (Temporal et al. 2014 c ). Once the number of the laser beams and their spatial distributions are defined, the model is solved by an iterative procedure.…”
Section: Optimal Laser Intensity Profilesmentioning
confidence: 99%
“…It has recently been shown that uniform solutions of the illumination model can be obtained for any general laser–capsule configuration (Temporal et al. 2014 c ). Once the number of the laser beams and their spatial distributions are defined, the model is solved by an iterative procedure.…”
Section: Optimal Laser Intensity Profilesmentioning
confidence: 99%
“…2002, 2004, 2007; Temporal & Canaud 2009, 2011; Temporal et al. 2011, 2014 a , b , c , d , 2015 a , b , c ; Canaud & Temporal 2010; Ramis et al . 2014, 2019) that can lead to different quantitative results.…”
Section: Introductionmentioning
confidence: 99%